2023
DOI: 10.3390/healthcare11121792
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Workplace Interventions to Improve Health and Well-Being of Health and Social Service Workers: A Narrative Review of Randomised Controlled Trials

Abstract: Health and social service workers face high levels of workload and job stressors, which can affect their health and well-being. Therefore, it is important to evaluate the effectiveness of workplace interventions that aim to improve their mental and physical health outcomes. This review summarizes the findings of randomized controlled trials (RCTs) that examined the impact of different types of workplace interventions on various health indicators among health and social service workers. The review searched the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 153 publications
1
3
0
4
Order By: Relevance
“…Ainda que a literatura existente estabeleça a eficácia de várias estratégias de promoção do adoecimento e de prevenção da saúde mental (SINGH; KUMAR; GUPTA, 2022), foi difícil encontrar artigos relacionados a intervenções de prevenção do adoecimento e da promoção da saúde mental de profissionais de enfermagem, por ser um tema negligenciado LAITINEN, 2023). As intervenções no local de trabalho devem ser implementadas como programas de rotina com horas de trabalho gratuitas, incentivar a participação ou integrar atividades de intervenção nas rotinas diárias de trabalho (SHIRI; NIKUNLAAKSO;LAITINEN, 2023).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ainda que a literatura existente estabeleça a eficácia de várias estratégias de promoção do adoecimento e de prevenção da saúde mental (SINGH; KUMAR; GUPTA, 2022), foi difícil encontrar artigos relacionados a intervenções de prevenção do adoecimento e da promoção da saúde mental de profissionais de enfermagem, por ser um tema negligenciado LAITINEN, 2023). As intervenções no local de trabalho devem ser implementadas como programas de rotina com horas de trabalho gratuitas, incentivar a participação ou integrar atividades de intervenção nas rotinas diárias de trabalho (SHIRI; NIKUNLAAKSO;LAITINEN, 2023).…”
Section: Discussionunclassified
“…A literatura destaca que algumas das barreiras comuns à participação em intervenções no local de trabalho entre profissionais de saúde envolvem tanto falta de pessoal adequado para propor as intervenções, bem como alta carga de trabalho, pressões de tempo, restrições de trabalho, falta de apoio do gestor, agendamento de programas de saúde fora do horário de trabalho e falta de motivação. Esta revisão sugere que as intervenções no local de trabalho têm pequenos efeitos positivos a curto prazo na saúde e no bem-estar dos cuidados de saúde trabalhadores (SHIRI; NIKUNLAAKSO;LAITINEN, 2023).…”
Section: Discussionunclassified
“…A systematic review with 39 studies by Montano et al investigated interventions aimed at improving organizational workplace conditions and showed that comprehensive interventions including multiple aspects like organizational and worktimerelated factors at the same time showed the highest success rates [40]. A recent narrative review with 108 randomized controlled intervention trials included 56 RCTs covering burnout and 14 RCTs covering psychosocial work stressors in healthcare workers concluded that there are frequent barriers to participate in workplace interventions (e.g., time pressure, no support by employers) and that most interventions only provided short-term benefits on mental health of healthcare workers [41].…”
Section: The Improvejob Trialmentioning
confidence: 99%
“…Cuantitativo El programa de intervención Prevail, mejora en la intervención grupal y reduce los niveles de estigma social y ausencia por enfermedad. Saju et al (31) (2019)…”
Section: Cualitativounclassified
“…2024; 4:718 6 fomentar lo positivo y controlar la enfermedad, pueden observarse excelentes evidencias respecto a la salud mental del trabajador. (31) Tabla 3. Programa Prevail Estigma hacia los demás Suposiciones erróneas acerca de enfermedades mentales de otras personas.…”
Section: Intervención Psicológicaunclassified